A new project launched to strengthen evidence use for African agriculture adaptation - Wanjiru, Anastacia; Njuguna, Lucy (2025)
As climate change intensifies across Africa, smallholder farmers are on the frontlines, facing increasingly extreme weather conditions. While climate mitigation has clear benchmarks, adaptation remains complex, often lacking reliable metrics to track progress. This gap has led to fragmented efforts and, in some cases, maladaptation, where interventions unintentionally heighten vulnerability.